Natural Products with Inhibitory Activity against Human Immunodeficiency Virus Type 1 - Maria S. Serna-Arbeláez; Laura Florez-Sampedro; Lina P. Orozco; Katherin Ramírez; Elkin Galeano; Wildeman Zapata (Advances in Virology)
Infections caused by human immunodeficiency virus (HIV) are considered one of the main public health problems worldwide. Antiretroviral therapy (ART) is the current modality of treatment for HIV-1 infection. It comprises the combined use of several drugs and can decrease the viral load and increase the CD4+ T cell count in patients with HIV-1 infection, thereby proving to be an effective modality. This therapy significantly decreases the rate of morbidity and mortality owing to acquired immunodeficiency syndrome (AIDS) and prolongs and improves the quality of life of infected patients. However, nonadherence to ART may increase viral resistance to antiretroviral drugs and transmission of drug-resistant strains of HIV. Therefore, it is necessary to continue research for compounds with anti-HIV-1 activity, exhibiting a potential for the development of an alternative or complementary therapy to ART with low cost and fewer side effects. Natural products and their derivatives represent an excellent option owing to their therapeutic potential against HIV. Currently, the derivatives of natural products available as anti-HIV-1 agents include zidovudine, an arabinonucleoside derivative of the Caribbean marine sponge (Tectitethya crypta), which inhibits the reverse transcriptase of the virus. This was the first antiviral agent approved for treatment of HIV infection. Additionally, bevirimat (isolated from Syzygium claviflorum) and calanolide A (isolated from Calophyllum sp.) are inhibitors of viral maturation and reverse transcription process, respectively. In the present review, we aimed to describe the wide repertoire of natural compounds exhibiting anti-HIV-1 activity that can be considered for designing new therapeutic strategies to curb the HIV pandemic.